Development of battery powered tricycle - Samurgam, Tilakiswaran (2007)
Electrical energy is one of alternative energy used in automotive industry now days. A battery is a device consisting of one or more electrochemical cells, which store chemical energy and make it available in an electrical form and used to move loads. Usage of electrical energy in automotive field has many advantages; it can reduce pollution, more quite and cheaper. The objective of this project is to design and develop a battery powered tricycle. The common problems faced by current tricycles have been identified. Methods of Finite Element Analysis (F.E.A) have been carried out to identify the strength of material .A prototype of Battery powered tricycle is fabricated at end of the period as a fulfilment of the project. Among the fabrication processes which are involve in this project are drilling, turning, bending and welding. The design and prototype of this project will be used to commercialize soon.